Overweight and Obesity Coexist with Thinness among Lao’s Urban Area Adolescents - Katiya Ivanovitch; Sonemany Keolangsy; Nontiya Homkham (Journal of Obesity)
Introduction. In recent decades, the developing countries of Southeast Asia, including the Lao People’s Democratic Republic (Lao PDR), have experienced a rapid growth of their urban population. Partly as a result of that, issues of undernutrition and overnutrition became a significant public health problem. Objective. To examine the prevalence of overweight and obesity and their related factors, among the school-attending adolescents in the Lao capital of Vientiane. Methods. A cross-sectional data on 300 adolescents aged 15–19 were collected during the months of March, April, and May 2018 by means of a self-administrated questionnaire. Anthropometric measurements were used to obtain data on height and weight. Pearson’s chi-squared test, Fisher exact tests, and univariable and multivariable logistic regressions were applied in the course of the statistical analysis. Results. The study found a high prevalence of overweight/obesity (23.3%) and thinness (10.3%). Poor eating habits were noted in 67.0% of adolescents, even though 78.0% of them had a good knowledge of nutrition. Factors significantly associated with the overweight/obesity were low physical activities (aOR = 18.3; 95% CI: 5.51–60.66) and adolescents living with their guardians (aOR = 0.25; 95% CI: 0.08–0.79). Results also indicated that, in 47.3% of the cases, teachers, acting as a source of health and nutrition information, can prevent the risk of adolescents’ overweight/obesity (aOR = 2.05, 95% CI = 1.11–3.80) but not their thinness (aOR = 0.4, 95% CI = 0.17–0.88). Conclusions. Laotian adolescents are facing the spectrum of malnutrition in urban areas. To improve adolescents’ nutritional status, there is a need for a collaborative approach of public health agencies that would address the issues of an effective food and nutrition policy. The school curricula should also include programs on nutrition and physical education.